1982
DOI: 10.1038/bjc.1982.77
|View full text |Cite
|
Sign up to set email alerts
|

High susceptibility of analbuminaemic rats to induced bladder cancer

Abstract: Images Figure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Recent studies revealed that NAR showed an extraordinary high susceptibility to N-butyl-N-(4-hydroxybutyl)-nitrosamine, a potent carcinogen. After feeding animals with this carcinogen for 8 weeks, 100% of NAR (16/16) and cancer within 20 weeks (82). High susceptibility of NAR to other carcinogens was also reported.…”
Section: Metabolic Perturbation Inmentioning
confidence: 92%
“…Recent studies revealed that NAR showed an extraordinary high susceptibility to N-butyl-N-(4-hydroxybutyl)-nitrosamine, a potent carcinogen. After feeding animals with this carcinogen for 8 weeks, 100% of NAR (16/16) and cancer within 20 weeks (82). High susceptibility of NAR to other carcinogens was also reported.…”
Section: Metabolic Perturbation Inmentioning
confidence: 92%
“…Using the maintenance of Con A agglutination of bladder cells as a marker, we examined the effects of 21 amino acids. The results indicated that L-isoleucine, Lleucine, and L-vallie behave like sodium saccharin and DL-tryptophan in maintaining agglutination (9). We describe here the promoting effects of L-isoleucine and L-leucine in 40to 60-week in vivo carcinogenesis experiments.…”
mentioning
confidence: 74%
“…NAR, derived from SD rats, also showed higher sensitivity in terms of invasion and malignancy than did the parent strain (6). In the previous reports, the sensitivities of female mice of 5 different strains (NJax, A W J a x , C3H/He, DAB/2, and C57BL/6) with regard to induction of nonpapillary invasive bladder carcinomas by BBN were comparable, with the exception of a low yield with the N J a x strain (8).…”
Section: Discussionmentioning
confidence: 94%